Implementation of digital fir filter in fpga - 457542 Chang, Chee Teong (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2002